Role of glycolysis in myeloid cells during dengue infection - Loy, Thomas (Nanyang Technological University, 2022)
There is no dengue virus (DENV) specific treatment, while there are several issues with the current dengue vaccines. Amongst blood cells, monocytes are the main target of DENV and monocytes interact with non-structural 1 (NS1) protein via TLR2/TLR4/TLR6 that might contribute to pathogenesis by supporting DENV replication and secreting inflammatory cytokines. Since DENV replication and induction of inflammatory cytokines in monocytes depend on glycolysis, we hypothesize that DENV induces metabolic rewiring in monocytes and targeting would ameliorate DENV pathogenesis. We show that in vitro DENV- infected monocytes upregulate glycolysis and inhibiting with 2-deoxy glucose (2DG) reduced DENV replication and production of TNF-α. Bioenergetics and RNAseq demonstrated induction of glycolysis in monocytes of thrombocytopenic patients. In vivo mouse experiments showed 2DG enhancing survival and lessens weight loss. 2DG also altered frequencies of classical and non-classical monocytes and reduces cytokine production from intermediate monocytes. Our study raises the possibility of altering host metabolism to treat DENV infection.